Avaliação do desenvolvimento motor de lactentes com baixo peso ao nascer e peso adequado ao nascer entre 6 e 12 meses de idade segundo a Escala de Desenvolvimento Motor de Alberta - Godoy, Vanessa Cristina Waetge Pires De [UNIFESP] (2019)
Introduction: Low birth weight (LBW) is established by the World Health Organization (WHO) as a birth weight less than 2500 grams, regardless of the gestational age and it is considered as a major public health problem associated with a series of short and long-term consequences including the risk of delayed motor development. Objective: To describe the motor development according to the Alberta Infant Motor Scale (AIMS) in infants born with low birth weight and adequate birth weight (ABW). Method: a cross-sectional study carried out between April 2016 and April 2017 with infants between 6 and 12 months age born with less than 2500 grams and followed up at the HSP / HU UNIFESP Low Birth Weight Clinic and a group of infants born with adequate birth weight enrolled in a Primary Health Care Unit at São Paulo’s metropolitan region. Variables: maternal conditions (socioeconomic, gestational intercurrences), birth (weight, gestational age, intercurrences) and infants (environmental and anthropometry). All children were evaluated with the Alberta Infant Motor Scale (AIMS) and the motor development was graded as normal (percentile> 25), suspect (percentile between 5 and 25) or abnormal (percentile <5). Results: 38 children from the LBW group and 60 children from the ABW group were evaluated. Socioeconomic characteristics and mother’s education from both groups were similar. Suspected or abnormal motor skills were observed in 18 (47.4%) and 26 (43.3%) children in the LBW and ABW groups, respectively. The highest percentage of suspected and abnormal motor skills was found in the group between 9 and 12 months old, with 54.6% in the LBW group and 58.8% in the ABW group. Conclusion: High suspicious or abnormal rates were observed in all the evaluated situations, with higher percentages between 9 and 12 months age.